Karakteristik Ketidakpatuhan Pekerja Harian Menggunakan Alat Pelindung Diri (APD) di Pabrik X tahun 2025 - Elisa Putri Agustin; Rini Handayani; Putri Handayani; Ade Heryana (Yayasan Literasi Sains Indonesia, 2026)
Based on observations and interviews conducted by the researcher in 2025 with 10 daily workers in the production department of Factory X, it was found that all workers (100%) exhibited poor behavior in the use of personal protective equipment (PPE), namely, they did not use PPE completely. Thru interviews, it was also found that there had been work accident incidents, such as a worker whose hand was blistered from being scalded by hot water from the boiler machine, preventing them from working for several months. There were also other workers who sustained hand injuries from the machine. This study aims to identify the characteristics of workers who do not comply with the use of PPE. This study uses a quantitative approach with a cross-sectional study design, and data collection was carried out thru questionnaires using the total sampling method. The population in this study includes all daily production workers at Factory X, totaling 51 people. The results of the univariate analysis show that 41 people (100% of respondents) are not compliant with the use of PPE. The characteristics of non-compliant workers are dominated by those aged ≥ 30 years, totaling 36 people (87.8%). By gender, most are male, with 34 people (82.9%). Meanwhile, there are 24 workers (58.5%) with a good level of knowledge. However, 26 workers (63.4%) show a poor attitude toward PPE use. From a supervision perspective, 23 people (56.1%) stated that supervision was good. Regarding the comfort of using PPE, 21 workers (51.2%) stated that they felt uncomfortable. Based on these findings, the researchers suggest that factory management issue warnings or sanctions to workers who do not comply with PPE usage rules, and conduct awareness campaigns.